Monitoring of subacute Wegener's granulomatosis clinically simulating seronegative spondylarthritis - A. A. Muradyants; E. I. Schmidt; M. E. Dmitrieva; E. S. Moskovikina (Медицинский совет, 2013)
Wegener's granulomatosis (WG) is a systemic vasculitis characterized by necrotizing granulomatous inflammation of small and medium-sized blood vessels and upper respiratory tract, lungs and kidneys [1]. WG is traditionally considered to be a a rare disease the prevalence of which is 25-60 people per 1 million of population; however, the last 30 years have seen a 4-fold increase in the incidence of the disease [2]. 90% of patients die within the first 2 years of the onset of the disease without treatment. Timely diagnosis of WG is therefore important because the disease if often hard to diagnose in the beginning due to atypical oligosymptomatic flow.